The fight of João Amaro: a rural worker in fight for rights (Pernambuco, years 1960) - Márcio Ananias Ferreira Vilela; Marcelo Góes Tavares (Clio: Revista de Pesquisa Histórica, 2017)
This article analyzes the experience of a rural worker who in 1965 appealed to the Labor Court in Pernambuco to claim the enforcement of rights already provided by law. We also analyze how the owners of the sugarcane mills made use of numerous mechanisms to circumvent labor laws, including appointing workers as agitators and subversives. In these cases, attempts were made to represent such rural workers as communist and dangerous subjects, which could disqualify their demands for rights in the Labor Court. Or it may have greater implications for the accused when considering the civil and military regime in Brazil, and the workers may be arrested and tortured, and in some cases even killed by the security and information agencies. In this way, the functioning of the Labor Court is defined and the plot in which the litigants are inserted in the political and rights struggles. As a documentary source for analysis, a labor process which compiles the collection of Labor Justice at the Federal University of Pernambuco.